Cholesterol-Based Grafted Polymer Brushes as Alignment Coating with Temperature-Tuned Anchoring for Nematic Liquid Crystals - Stetsyshyn, Yurij (Langmuir : the ACS journal of surfaces and colloids, 2016)
Novel alignment coating with temperature-tuned anchoring for nematic liquid crystals (NLCs) was successfully fabricated in three step process, involving polymerization of poly(cholesteryl methacrylate) (PChMa) from oligoproxide grafted to the glass surface premodified with 3-aminopropyltriethoxysilane. Molecular composition, thickness, wettability of the PChMa coating and its alignment action for a NLC were examined with time of flight-secondary ion mass spectrometry, ellipsometry, contact angle measurements, polarization optical microscopy and commercially produced PolScope technique allowing for mapping of the optic axis and optical retardance within the microscope field view. We find that the PChMa coating provides a specific monotonous increase (decrease) in the tilt angle of the NLC director with respect to the substrates normal upon heating (cooling) referred to as anchoring tuning